A Novel Fuzzy Probabilistic Clustering Algorithm for Satellite Image Segmentation - Mantilla, L (2018)
The authors would like to thank Consejo Nacional de Ciencia, Tecnolog´ıa e Innovacion Tecnol ´ ogica ´ , Peru (CONCYTEC), Fondo Nacional de Desarrollo Cient´ıfico y Tecnologico ´ , Peru (FONDECYT) for the financial support; and Autoridad Nacional del Agua, Peru (ANA) for providing the satellite images.